Trade and development directions for the 21st century - Toye, J. F. J.; United Nations Conference on Trade and Development; Edward Elgar Publishing (Cheltenham, U.K. ; Northampton, Mass. : Edward Elgar, 2003)
This book questions what enduring lessons have been learnt about the interdependence of international trade and economic development during the last 50 years. Since the end of the Cold War and the advent of the WTO, developing countries have been forced to face the choice of whether, and to what extent, to integrate economically with the rest of the world. The key issue of international political economy is emphasized.
1. Introduction -- 2. The historical conflict of socialism and capitalism, and the post-socialist transformation -- 3. Globalization and development strategies -- 4. Trade policy as development policy : building on fifty years' experience -- 5. Industrialization under new WTO law -- 6. Technological change and opportunities for development as a moving target -- 7. Financing for development : current trends and issues for the future -- 8. Agricultural trade barriers, trade negotiations and the interests of developing countries -- 9. Economic dependence on commodities -- 10. Income distribution and development -- 11. Order, the rule of law and moral norms -- 12. Regional cooperation in a changing global environment : success and failure of East Asia -- 12. Economic governance institutions in a global political economy : implications for developing countries.
"The work is published for and on behalf of the United Nations".
Papers presented at a round table of eminent economists at the opening session of UNCTAD X in Bangkok, Thailand, 2000.
Includes bibliographical references and index.
Keywords: International trade -- Congresses; Economic development -- Congresses; Economic history -- 1990 -- Congresses; Electronic books